THE FUNCTION OF THE AUTHOR’S SPEECH AND DIALOGICAL FORMS OF SPEECH IN HISTORICAL NOVELS - Jurayeva, Shalolakhan (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The article presents examples of author's speech in fiction and historical novels, the role of dialogic speech in the form of communication, historical formation, tasks, structure, types of language, functions of speech in fiction, as well as the opinions and conclusions of famous researchers.